The Effect of Telephone Nursing Follow-up on Self-Efficacy of Females With Type 2 Diabetes Mellitus - Nahid Mohammadi; Roya Soleymani; Afsar Omidi; Ghodratolah Roshanae (Hamadan University of Medical Sciences, 2017)
Introduction: Diabetes is a common and costly disease. Nursing care services are both effective in reducing costs and improving the quality of life and the relationship between patients and nurses. The aim of this research was to investigate the effect of telephone nursing follow-up on self-efficacy in females with type 2 diabetes mellitus in Hamadan. Methods: This study had a quasi-experimental, pretest, and post-test design and was conducted on 109 females with type 2 diabetes (55 patients in the intervention group and 54 in the control group), in the city of Hamedan. Samples were selected by randomized block permutation. Information required by the questionnaire was obtained through 10 questions in three sections on demographic characteristics, general health questionnaire (r = 0.9) with 28 questions on diabetes management, and Self-Efficacy Scale (r = 0.93) with 19 questions. The experimental group received telephone counseling and follow-up intervention for 12 weeks. Data was analyzed using SPSS-16, and descriptive and inferential statistics. Significance level of 5% was considered. Results: Average self-efficacy score in the control group, before and after the follow-up was 117.35 ± 37.52 and 117.53 ± 37.33 and in the experimental group these values were 122.05 ± 36.41 and 163.03 ± 9.93, respectively. In the experimental group, self-efficacy was significantly increased after the intervention (P < 0.001). Conclutions: According to our findings, it could be concluded that telephone nursing follow-up was effective in improving self-efficacy in females with diabetes.